2016
DOI: 10.6061/clinics/2016(06)02
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study evaluating the correlation between the severity of intervertebral disc injury and the anteroposterior type of thoracolumbar vertebral fractures

Abstract: OBJECTIVE:To evaluate the correlation between the severity of intervertebral disc injury and the anteroposterior type of thoracolumbar vertebral fractures.METHODS:Fifty-six cases of thoracolumbar vertebral fractures treated in our trauma center from October 2012 to October 2013 were included in this study. The fractures were classified by the anteroposterior classification, whereas the severity of intervertebral disc injury was evaluated using magnetic resonance imaging. The Spearman correlation coefficient wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 17 publications
3
11
0
Order By: Relevance
“…Our study is advantageous because it investigated the association between kyphotic deformity and factors that can be evaluated on initial MRI scans, which are routinely performed in the assessment of spinal injuries. [ 21 , 22 ] Specifically, we used MRI scans to grade IDIs according to Sander's classification to investigate the correlation between IDI severity and fracture type. However, we could not find any correlation between kyphosis and these 2 factors.…”
Section: Discussionmentioning
confidence: 99%
“…Our study is advantageous because it investigated the association between kyphotic deformity and factors that can be evaluated on initial MRI scans, which are routinely performed in the assessment of spinal injuries. [ 21 , 22 ] Specifically, we used MRI scans to grade IDIs according to Sander's classification to investigate the correlation between IDI severity and fracture type. However, we could not find any correlation between kyphosis and these 2 factors.…”
Section: Discussionmentioning
confidence: 99%
“…As the severity of the fracture increases, the form of intervertebral disc injury can also manifest as intervertebral disc edema, intradisc hemorrhage, the nucleus pulposus protruding into the vertebral body, or even a complete tear. In our previous study, we also found that the severity of the injury to the adjacent intervertebral disc in thoracolumbar fractures was positively correlated with the type of Magerl AO fracture [17]. When the nucleus pulposus protrudes into the vertebral body, the volume of the intervertebral disc decreases, the height of the intervertebral space decreases, and the pressure in the vertebral body increases, which breaks the balance of the pressure difference between the subchondral bone and cartilage endplate and then affects the diffusion of nutrients to the intervertebral disc, leading to intervertebral disc degeneration.…”
Section: Discussionmentioning
confidence: 68%
“…In our study, the non-fusion procedures were not an optimal option for their treatment. Also, the literature suggested fused schemes only after an abnormal signal of intervertebral disc was prominent [7,11]. Hence, we proposed the selective fusion or limited fusion schemes for the TLF with short-segment instrumentation, i.e., the vertebrae above and below the fractured vertebrae that preserved not only the motion of the spine postoperatively but also, stabilized the fracture, and restored the spinal alignment.…”
Section: Discussionmentioning
confidence: 99%
“…However, the best treatment and surgical indications of TLF, especially for the fusion procedure are still controversial [4][5][6]. Fusion generates de nite immediate bene ts and late stability, such as vertebral body height loss beyond 40%, an abnormal signal in the intervertebral disc, and rupture of the inter-spinal ligament [7]. Although the fusion of mobile segments solves the problem of instability, it restricts the movement of the spine.…”
Section: Introductionmentioning
confidence: 99%